ANALISIS FAKTOR- FAKTOR YANG MEMPENGARUHI MINAT NASABAH ATAS TABUNGAN WADI’AH - Wardatul Jannah; Nur Diana; Muhammad Cholid Mawardi (Universitas Islam Malang, 2019)
ABSTRACTThis study aims to determine the effect of profit sharing, service, religion and motivation on customer interest in Wadi'ah savings with as many as 100 customers from Syari'ah Mandiri Bank and Syari'ah BRI Bank. This study uses descriptive quantitative methods. The results of this study show that the profit sharing, service, and religious variables have a significant effect on customer interest in Wadi'ah savings, but one of the variables is that the motivation variable does not have a significant effect because the significance value is greater than 0.05. the value of probability and its significance, profit sharing (0.047 <0.05), service (0.001 <0.05), religion (0.001 <0.05), and motivation (0.895> 0.05). The value of R square = 0.513, which means that 51.3% of customer interest in Wadi'ah's savings is influenced by profit sharing, service, and religion. Based on these results, the alternative hypothesis Ho is rejected and Ha is accepted. Keywords: Profit Sharing, Service, Religion, Motivation, Mandiri Syari'ah, BRI Syari'ah.